Struktur Ide Dasar Pemikiran Pendidikan Sayyid Muhammad bin Alawi al-Maliki - Muhammad Budi Sulaiman; Ahmad Zaeni; Dewi Purwanti (AL-MUFASSIR, 2021)
The present study scrutinizes Syekh Muhammad bin Alawi al-Maliki’s standpoints by using the framework of Islamic education philosophy. This study employs a qualitative study by using inductive method (istiqra). The data collected are in form of Syekh Muhammad’s viewpoints concerning education from which his basic ideas regarding education are constructed as a foundation of Islamic education philosophy. The findings indicate that, according to Sheikh Muhammad, human are created through soil and spirit blown by Allah SWT hence they consist of potential, remarkable, and perfect body and spirit. In addition, in line with Sheikh Muhammad, the essence is belief and insights regarding current occurrences originated from the revelation and reason to attain convincing and relevant knowledge with current circumstances. The essence of the uppermost value for him is the Rabbani value and the result of reason such as theoretical, economic, social, and political values.